(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aimed to describe the meaning of the idiomatic expression in The Boss Baby Movie by Tom McGrath. This research used descriptive qualitative method. The research explain or describe about the meaning of idiomatic expression that found in The Boss Baby Movie by Tom McGrath. The data collected through conversation or dialogue in The Boss Baby Movie by Tom McGrath. The result of this research showed that there were 3 different type of the meaning according to Geoffry Leech theory’s, 30 idiomatic expression found in The Boss Baby Movie there are 25 idiomatic expression with conceptual meaning, 4 idiomatic expression with connotative meaning and 1 idiomatic expression with reflected meaning.